The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1536/ihj.46.339
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Renin-dependent Renovascular Hypertension Successfully Treated With Percutaneous Transluminal Renal Angioplasty and Stenting

Abstract: SUMMARYA 37-year old woman was suspected of having renovascular hypertension because of recent onset severe hypertension (blood pressure 220/135 mmHg; compared to 132/65 mmHg two years earlier) and an abdominal bruit. A captopril renal scan indicated the presence of right renal artery stenosis. Additionally, a captopril plasma renin activity (PRA) provocation test showed a positive result for renovascular hypertension (baseline PRA = 291 µU/mL; 1 hour post-captopril PRA = 1444 µU/mL). Selective renal angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The elevated blood pressure response in renal artery stenosis (RAS) is predominantly attributed to the increased renin secretion from the diseased kidney . Renal vein renin sampling has been demonstrated in some studies as a clinical tool to assess the physiological significance of stenosis in the renal artery . Elevated renin mediates hypertension through activation of the renin aldosterone and the lipoxygenase pathway .…”
mentioning
confidence: 99%
“…The elevated blood pressure response in renal artery stenosis (RAS) is predominantly attributed to the increased renin secretion from the diseased kidney . Renal vein renin sampling has been demonstrated in some studies as a clinical tool to assess the physiological significance of stenosis in the renal artery . Elevated renin mediates hypertension through activation of the renin aldosterone and the lipoxygenase pathway .…”
mentioning
confidence: 99%
“…However, Fang et al reported a case of renovascular hypertension in which both the blood pressure and PRA were normalized using PTRA ( 22 ). In the present study, although antihypertensive agents used varied among individuals, no significant differences were noted in the specific medications used in the responder group versus the non-responder group.…”
Section: Discussionmentioning
confidence: 99%